2006 IEEE 63rd Vehicular Technology Conference
DOI: 10.1109/vetecs.2006.1683168
|View full text |Cite
|
Sign up to set email alerts
|

Some Statistical Properties of Multicarrier Signals and Related Measures

Abstract: In this paper we study some statistical properties of a multicarrier signals using the order statistics. Analytical expressions for the probability density function of different order statistics of a sampled OFDM system is presented. We then find the amount of power which is clipped from each order of the signal when the signal is passed through a clipping nonlinearity. This is used to represent the relevance of peak-to-average power ratio (PAPR) to evaluate the effect of nonlinearity on the performance of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…VIP has been shown to be a much better measure of a multicarrier signal's sensitivity to nonlinear distortion than is PAPR [14]. Our results apply to zero excess bandwidth signals with contiguous spectra.…”
Section: Introductionmentioning
confidence: 71%
“…VIP has been shown to be a much better measure of a multicarrier signal's sensitivity to nonlinear distortion than is PAPR [14]. Our results apply to zero excess bandwidth signals with contiguous spectra.…”
Section: Introductionmentioning
confidence: 71%
“…However, we showed that the effect of a nonlinearity on an OFDM signal is not clearly related to its PAPR. In some recent contributions other measures of the envelope fluctuations of multicarrier signals, such as the cubic metric (CM) [11,12] and the variance of the instantaneous power (VP) [13], have been proposed. The motivation for CM relies on the fact that the major distortion is caused by the third-order intermodulation product while the motivation for VP metric is to reduce the envelope fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [13] it is shown that, except for large back-offs, CM and VP are more related to the amount of distortion introduced by a nonlinearity than PAPR. Moreover in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the proposed MM-CI-based optimization procedure can be summarized in Algorithm 1. To solve the problems (40) and (41), we adopt CVX, a package for specifying and solving convex programs [48]. The tolerant precision for the stopping criteria of the CI process and the MM process are denoted by ε CI > 0 and ε MM > 0, respectively.…”
Section: A Choices Of Osbep Upper Bound and Initial Point In (40)mentioning
confidence: 99%